PENGARUH GREEN ACOUNTING TERHADAP PERTUMBUHAN LABA DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MEDIASI - Magfiroh, Argik Fitro; Indira, Irma; Dilasari, Aranta Prista (Jurnal Bina Bangsa Ekonomika, 2025)
This research aims to determine the effect of Green Acounting on profit growth with company size as a mediating variable. The object of this research is all mining companies listed on the IDX. The sample in this study consists of 13 mining companies listed on the Indonesia Stock Exchange (IDX) during the period 2021-2023, with a total of 39 annual financial statements used. This research uses secondary data, and the sampling technique employed in this study is purposive sampling. This research uses the Partial Least Square (PLS) approach with the SmartPLS Version 3.0 application. The results of this study indicate that Green Acounting does not affect profit growth, Green Acounting significantly affects the size of the Company, the Company does not affect profit growth, and the size of the Company is unable to mediate the effect of Green Acounting on profit growth